The effectiveness of the modified learning cycle and brainstorming strategies in the achievement of students of teacher education institutes in the subject of history and the development of their self-confidence - Hasan, Ali Knewr; Nafl, Shatha Qasim (Al-Adab Journal, 2015)
Educatorsefforts to search for strategies that have proven research and observations field , that the rehabilitation of the students without the required level , which it a lot of the frustrated and lack of self .Confidence whiletechingassignment, so the researchers tried to work out in this study (the effectiveness of the strategies of the learning cycle ended , and brain storming in the collection of students institutes prepare teachers in history and the development of self-confidence )and to identify the impact. Put researchers zero the following assumptionsNostisticallysignificant differences at the level of the significance (50.0)between the average score for students of the first experimental group who study of history by using strategic learning cycle amended, and the average score for students of the second experimental who are studying the use of strategy brain storming , and theaverage score for the control group students in test self-assurance.To investigate , the researchers determined empirically follow partial set of three experimental group of test dimensions in achievement and self-confidence and was chosen in deliberate research sample of students from the third stage in thepreparation of teachers in the institute of the general directorate for educational Baghdad the first rusafa.Total sample (30 students) and by(10) students pergroup, and rewarded students between research group in thevariables (previous academicachievement,intelligence, prior knowledge , self-confidence the previous test , adjust the variables imaginary .Promising researchers (100) requirement behaviorally covered the first three quarters of the material modern and contemporary history ,promising plans for teaching specific subjects for student research group at the end of the experiment ,which lasted an entire semester included on the achievement test 40 forty –paragraph- type multiple choice test has been characterized by honesty and consistency , and the researchers adopted a measure ofself-confidence, prepared (Mehdawi) and adopted byjafarjawad jabber in 1993 because it is compatible with the current sample._ Superiority of the two experimental group , whichexamined the learning cycle in accordance with the revised strategy and brainstorming on the control group , who studid according to the traditional way of the achievement test posttest ._ Superiority of the twoexperimentalgroup, which examined the learning cycle in accordance with the revised strategy and brainstorming on the control group, who studid according to the traditional method of testing self- confidence._ The presence of statisticallysignificant difference between pre and post testand for the benefit of students at posttest tow experimental group